General Features of the Economy in the Arabian Peninsula Before Islam (Comprehensive Journal of Science, 2026)
The research manipulates the main climatic features that dominated the Arabian Peninsula during the Fifth Century A.H.. and its impact on the Bedouins who inhabited the desert lands. The research focuses as a case study. \\ The significance of the research can be seen on its concenlration on a relative short historical period, that has its obvious association with the alienation  and the climatical changes, which resulted in essential changes in the economical ways of life, and a basic transformation in alliance, and political affiliation in Arabian Peninsula. \\ The topic has not been dealt widely among the scholars, concentrates chiefly on climatical conditions within the Arabian Peninsula before the alienation, and sheds a light on the literally and folkloric studies of the nomads outside the Arabian Peninsula. All these elements constitute to its complexity and significance. \\ The research sheds a light on sever climatic conditions that hit the desert belt of the Arabian Peninsula, and hence affected passively on tribe, whose economy is a nomadic one, basing on herding the camels. This type of economy is affected by the climate and the availability of pasture. The sever climatic condition that appeared during the Fifth Century A H. has its negative impact particularly their subsistence economy, raising of the price, and the scarcity of food. \\ It is worth mentioning that the climatic changes of the Arabian Peninsula had also been associated with a political sphere, in terms of the division of Al-Mosowiya Emirate in Belad Al-Hijaz during the regime These environmental and political factors had contributed largely to enforce a number of Arabian Peninsula nomads to leave their home lands else where. \\ The Ethno-historic approach has been adopted in this study, in terms of environmental correlation that exists between the man and the adaptation process within the spatial and historical distribution of the settlers. From an economical viewpoint the study has also adopted an uncomplicated subsistence strategic way of life, that relies on unfixed natural resources within a fluctuated climatic condition. Although the interpretation of the historical events basing on climatic factors is not always the ideal approach, but it works out.